Development and evaluation of an instructional kit for integrating ecological issues in high school biology - Aunzo, Melinda M. (1984)
The purpose of this study was to develop, try out and evaluate an instructional kit for integrating ecological issues in high school biology. The results showed that the instructional kit was a more effective teaching material for integrating ecological issues in high school biology than the textbooks. Both the textbooks and the instructional kit were similarly effective in developing attitude of the students toward ecological issues. There were no significant differences in the attitude and achievement of the males from that of the females who used the instructional kit.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Ecology -- Study and teaching (Secondary) -- Philippines; Biology -- Study and teaching (Secondary) -- Philippines; Teaching -- Philippines -- Aids and devices